Sebaran Pelagis Besar Hasil Tangkapan Purse Seine di Indonesia - Ratu Sari Mardiah; Yaser Krisnafi; Tyas Dita Pramesthy (JSIPi (JURNAL SAINS DAN INOVASI PERIKANAN) (JOURNAL OF FISHERY SCIENCE AND INNOVATION), 2023)
Purse seine catches that have high economic value are big pelagic whose distribution of fishing areas and landing sites are poorly known. This study aims to find out the distribution of large pelagic purse seine catches based on WPP and their landing ports. The data used is data of purse seine catch from the Ministry of Maritime Affairs and Fisheries of the Republic of Indonesia in 2019 and 2020 to be analyzed descriptively. The results showed that four big pelagic species caught by purse seines: tuna (Thunnus sp.), mackerel (Scomberomorus commerson), marlin (Istiophorus platypterus) and swordfish (Xiphias gladius). Tuna is caught in all WPP and landed at 62 fishing ports. Mackerel was also caught in all WPP and landed at 74 fishing ports. Marlin were caught at 10 WPP and landed at 27 fishing ports. Swordfish were caught in 4 WPP and landed at 5 fishing ports. Knowledge on distribution of big pelagic purse seine catches based on WPP and landing ports can be used as a basis for evaluating measured fishery policies in terms of catch landing relating to fishing areas.